Finite Elements Analysis of Large Marine Crown Gear Coupling - Su Jinzhan; Yang Xiaohui; Guan Yabin; Liu Guanglei (Jixie chuandong)
Considering that the simplified formula of the gear handbook or the general crown gear coupling are not suitable for the design of the large marine crown gear coupling,an analytical system of the crown gear coupling is developed. Taking a marine crown gear coupling as an example,the model of crown gear coupling with high accuracy is established by the analytical system. Then,the model data is imported into the ANSYS software,the finite element analysis of gear teeth is carried out,and the distributions and trend of variation of the tooth stress under alignment and limit misalignment conditions are obtained,the basis for the design of the large marine crown coupling is provided.